2023
DOI: 10.3390/foods12040826
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Capsid and Genomic Integrity Tests on Norovirus Extraction Recovery Rates

Abstract: Human norovirus (HuNoV) is the leading pathogen responsible for food-borne illnesses. However, both infectious and non-infectious HuNoV can be detected by RT-qPCR. This study evaluated the efficiency of different capsid integrity treatments coupled with RT-qPCR or a long-range viral RNA (long RT-qPCR) detection to reduce the recovery rates of heat inactivated noroviruses and fragmented RNA. The three capsid treatments evaluated (RNase, the intercalating agent PMAxx and PtCl4) reduced the recovery of heat inact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…In the literature, the efficacy of RNases to degrade RNA from inactivated viruses varies, with some studies reporting successful degradation [ 44 , 58 , 60 ], while others found less favorable results [ 56 , 57 , 88 ]. These discrepancies could be due to variations in RNase concentrations, incubation times, sample types, and virus types [ 46 , 56 , 59 , 60 , 62 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the literature, the efficacy of RNases to degrade RNA from inactivated viruses varies, with some studies reporting successful degradation [ 44 , 58 , 60 ], while others found less favorable results [ 56 , 57 , 88 ]. These discrepancies could be due to variations in RNase concentrations, incubation times, sample types, and virus types [ 46 , 56 , 59 , 60 , 62 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Platinum compounds have recently been used to evaluate virion integrity of viruses such as SARS-CoV-2, norovirus, hepatitis A virus and HEV [ 41 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. However, the efficiency of the applied technique varies across viruses, virus concentration, virus sample and inactivation techniques.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The detection of NoV in both food and environmental samples remains a significant challenge, primarily due to the complex composition of sample tissues and the low concentration of the virus present. Current human NoV cell culture systems are complicated and do not allow infectious NoV detection at levels found in contaminated foods [ 16 ]. Similarly to other viruses, detecting and monitoring NoV RNA encompasses several steps, including sample collection, concentration and enrichment, laboratory assay, and data normalization and interpretation.…”
Section: Introductionmentioning
confidence: 99%